2012
DOI: 10.1038/nm.2756
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB–inducing kinase (NIK) promotes hyperglycemia and glucose intolerance in obesity by augmenting glucagon action

Abstract: The canonical IKKβ/NF-κB1 pathway has been well documented to promote insulin resistance; however, the noncanonical NIK/NF-κB2 pathway is poorly understood in obesity. Additionally, the contribution of counterregulatory hormones, particularly glucagon, to hyperglycemia in obesity remains unclear. Here we show that NIK promotes glucagon responses in obesity. Hepatic NIK was abnormally-activated in mice with dietary or genetic obesity. Systemic deletion of NIK decreased glucagon responses and hepatic glucose pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 37 publications
4
97
0
1
Order By: Relevance
“…Although both are activated by TNF-α, they were reported to have opposite activities in the regulation of the cAMP signaling pathway. NIK upregulated the pathway by direct phosphorylation of the CREB protein in a study of glucagon signaling in liver (26). IKKε downregulated the pathway through induction of PDE3B activity in a study of IKKε in adipocytes (27) in which IKKε was found to phosphorylate the PDE3B protein.…”
Section: Discussionmentioning
confidence: 99%
“…Although both are activated by TNF-α, they were reported to have opposite activities in the regulation of the cAMP signaling pathway. NIK upregulated the pathway by direct phosphorylation of the CREB protein in a study of glucagon signaling in liver (26). IKKε downregulated the pathway through induction of PDE3B activity in a study of IKKε in adipocytes (27) in which IKKε was found to phosphorylate the PDE3B protein.…”
Section: Discussionmentioning
confidence: 99%
“…However, chronic inflammation in the liver causes insulin resistance, leading to increased HGP (79). Liver inflammation also increases the ability of glucagon to stimulate HGP (36, 234). …”
Section: Liver Glucose Metabolismmentioning
confidence: 99%
“…Since inflammation promotes insulin resistance, a driving force for type 2 diabetes, the H-lipid subpopulation is also likely to contribute the pathogenesis of type 2 diabetes by stimulating the production of proinflammatory cytokines. These cytokines may increase the ability of the L-lipid subpopulation to produce glucose by increasing insulin resistance and/or by increasing the hyperglycemic response to glucagon as we recently reported (23).…”
Section: Discussionmentioning
confidence: 68%